Tumor growth inhibition and immune system activation following treatment with thorium-227 conjugates and PD-1 check-point inhibition in the MC-38 murine model - Berg-Larsen, Axel; Mobergslien, Anne; Moen, Ingrid; Petros, Gebregziabher; Kristian, Alexander; Gunvaldsen, Kristine Sponheim; Cruciani, Véronique; Wickstroem, Katrine; Bjerke, Roger Malerbakken; Karlsson, Jenny; Cuthbertson, Alan (Frontiers in Medicine, 2022)
Targeted thorium-227 conjugates comprise the combination of a monoclonal antibody with specificity for a tumor cell antigen and a 3,2-HOPO chelator enabling complexation of thorium-227 (Th-227). The radiolabeled conjugate functions as an effective delivery system of alpha-particle radiation to the surface of the tumor cell inducing difficult to repair complex DNA damage and cell death. In addition, the mechanism of action of targeted alpha therapy (TAT) appears to involve a significant component linked to stimulation of the immune system. We report herein evidence of immune activation and long-lasting immune protection of a TAT in a syngeneic model using the MC-38 murine cell line. Firstly, MC-38 cells were irradiated ex vivo with the thorium labeled antibody before subcutaneous implantation into mice. These mice were then rechallenged with MC-38 cells contra-laterally. In the group receiving irradiated cells, 9 out of 10 animals had no measurable tumor growth compared to aggressive tumor growth in the control group. Secondly, in an efficacy study, 500 kBq/kg of thorium labeled antibody alone or in combination with PD-1 checkpoint inhibitor gave statistically significant tumor growth inhibition compared to vehicle control. Animals with no measurable tumors were once again rechallenged contra-laterally with MC-38 cells. The re-growth of tumors was significantly delayed (approx. 60 days) in the treatment group compared to age-matched controls (approx. 30 days) in the monotherapy group. Interestingly, in the TAT/ PD-1 combination group no re-growth was observed demonstrating the potential of combining a TAT with checkpoint inhibition therapy. Finally, tumors were excised from treated mice and analyzed by flow cytometry and immunohistochemistry (IHC). Analysis revealed significant infiltration of CD8+ T-cells and mature dendritic cells compared to vehicle controls. Together these results indicated that an ongoing immune response from treatment with alpha radiation could be enhanced by check-point inhibition.